Assessing tertiary students’ awareness, acceptance, and use of generative artificial intelligence as a tool for academic work - Ayeh, Isaac Gyan; Kumah, Modestus (International Journal of Educational Technology and Learning, 2026)
Generative Artificial Intelligence, such as ChatGPT, has garnered significant attention and profoundly impacted human lives in various ways, including the education sector. Higher education increasingly uses artificial intelligence (AI), which offers several advantages for revolutionizing teaching and learning. Despite the global call for GenAI and its wide potential benefits in education, a significant empirical gap remains in understanding how students specifically perceive, accept, and use GenAI tools in their academic work. The researchers employed a mixed-methods sequential explanatory design to investigate tertiary students' awareness, acceptance, and use of GenAI tools, such as ChatGPT and other AI-powered platforms, in their academic assignments. The study found a generally high level of acceptance of GenAI among tertiary students. Gender plays a significant role in the adoption and use of GenAI among Tertiary students. Age and degree type were statistically insignificant predictors of GenAI use among tertiary students. The tertiary students use GenAI tools for various tasks, including answering academic questions, Conducting Research, summarizing, Brainstorming and Idea Generation, generating academic ideas, Supporting Mathematics, and essay writing. The researchers recommend that tertiary institutions and stakeholders provide formal training and policies on the ethical use of GenAI in education.